O princípio de razão, o utilitarismo e o antiutilitarismo - Caillé, Alain (2001)
In this article, it's demonstrated how certain notions derived from the Rationalism and utilized in Social Sciences are strongly determinated by the utilitarian tradition and, therefore, the very concept of rationality, in practice, bears uncertain limits given its subordination to the concept of interested calculation. Criticism aiming at the utilitarian rationality is complex as far as different meanings for utilitarism are at stake: a practical level, such as the economical utilitarism preaching the satisfaction of primary and egoistic material interests; a theoretical level, proposing that all human beings are, by nature, egoistic and calculators; and a normative level, creating a tie between Justice and the satisfaction of a huger number of individuals. Criticism to these thesis leads the author to remind Marcel Mauss contribution to settle a new paradigme based on the concept of donation. Mauss' text is a fundamental one to understand the passage of a antiutilistarist negative criticism to another antiutilitarist positive criticism, supported by this new paradigme.